2021
DOI: 10.1107/s2053230x21007263
|View full text |Cite
|
Sign up to set email alerts
|

LrpCBA pilus proteins of gut-dwelling Ligilactobacillus ruminis: crystallization and X-ray diffraction analysis

Abstract: Adhesion to host surfaces for bacterial survival and colonization involves a variety of molecular mechanisms. Ligilactobacillus ruminis, a strict anaerobe and gut autochthonous (indigenous) commensal, relies on sortase-dependent pili (LrpCBA) for adherence to the intestinal inner walls, thereby withstanding luminal content flow. Here, the LrpCBA pilus is a promiscuous binder to gut collagen, fibronectin and epithelial cells. Structurally, the LrpCBA pilus displays a representative hetero-oligomeric arrangement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 58 publications
0
0
0
Order By: Relevance
“…Mass-spectrometric analysis, size-exclusion chromatography and SDS-PAGE analysis confirmed that the purified 49 kDa LrpA F was pure, homogeneous and in a monomeric form in solution (Prajapati et al, 2021). As part of the structure determination, a truncated and stable 30 kDa fragment of LrpA (LrpA T ) was also generated by limited proteolysis with subtilisin and was then purified using the aforementioned purification protocol for LrpA F (Prajapati et al, 2021). LrpA F was also purified by exchanging the buffer with 0.1 M sodium acetate pH 4.8, 150 mM NaCl during size-exclusion chromatography to check the effect of pH on the oligomerization state and conformational changes.…”
Section: Macromolecule Productionmentioning
confidence: 78%
See 4 more Smart Citations
“…Mass-spectrometric analysis, size-exclusion chromatography and SDS-PAGE analysis confirmed that the purified 49 kDa LrpA F was pure, homogeneous and in a monomeric form in solution (Prajapati et al, 2021). As part of the structure determination, a truncated and stable 30 kDa fragment of LrpA (LrpA T ) was also generated by limited proteolysis with subtilisin and was then purified using the aforementioned purification protocol for LrpA F (Prajapati et al, 2021). LrpA F was also purified by exchanging the buffer with 0.1 M sodium acetate pH 4.8, 150 mM NaCl during size-exclusion chromatography to check the effect of pH on the oligomerization state and conformational changes.…”
Section: Macromolecule Productionmentioning
confidence: 78%
“…Size-exclusion chromatography was then performed using a HiPrep 26/60 Sephacryl S-200 column (GE Healthcare) with Tris buffer (see above). Mass-spectrometric analysis, size-exclusion chromatography and SDS-PAGE analysis confirmed that the purified 49 kDa LrpA F was pure, homogeneous and in a monomeric form in solution (Prajapati et al, 2021). As part of the structure determination, a truncated and stable 30 kDa fragment of LrpA (LrpA T ) was also generated by limited proteolysis with subtilisin and was then purified using the aforementioned purification protocol for LrpA F (Prajapati et al, 2021).…”
Section: Macromolecule Productionmentioning
confidence: 90%
See 3 more Smart Citations